AMANAH AS A VALUE IN ZAKAT MANAGEMENT ACCOUNTING - Muryani Arsal; Khalishah Ulfah; Muchriana Muchran (Imanensi: Jurnal Ekonomi, Manajemen, dan Akuntansi Islam, 2022)
This study aims to determine the accounting practices of zakat management in zakat management bodies. Descriptive qualitative was chosen to explain zakat management accounting with trust metaphor. The National Amil Zakat Agency (BAZNAS) of Makassar City and Wahdah Inspirasi Zakat (WIZ) of Jeneponto Regency were selected as research objects. The results showed that the accounting for the management of the Makassar City National Amil Zakat Agency and Wahdah Inspirasi Islamiyah Jeneponto Regency was a process of collecting, distributing, and utilizing zakat which was carried out with the characteristics of trust. To increase public trust, amil must apply a trustful approach in recognizing, measuring, disclosing, and presenting zakat received from muzakki. Abstrak This study aims to determine the accounting practices of zakat management in zakat management bodies. Descriptive qualitative was chosen to explain zakat management accounting with trust metaphor. The National Amil Zakat Agency (BAZNAS) of Makassar City and Wahdah Inspirasi Zakat (WIZ) of Jeneponto Regency were selected as research objects. The results showed that the accounting for the management of the Makassar City National Amil Zakat Agency and Wahdah Inspirasi Islamiyah Jeneponto Regency was a process of collecting, distributing, and utilizing zakat which was carried out with the characteristics of trust. To increase public trust, amil must apply a trustful approach in recognizing, measuring, disclosing, and presenting zakat received from muzakki.